2017
DOI: 10.1017/mor.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Justice Climates and Management Team Effectiveness: The Central Role of Group Harmony

Abstract: Although social harmony is one of the most important cultural values in many of Asian societies it has rarely been studied in the mainstream management literatures. Based on the group-value theory of justice we examined how group justice climates influence group effectiveness through group harmony. Analyses of data on 106 upper-level management teams from Chinese organizations showed that justice climates were positively associated with group harmony, which in turn was positively associated with team task perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 91 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Given these ethical goals are not inherently contradictory, future research may explore boundary conditions under which ethical dilemmas could be creatively resolved in a win-win fashion. For example, research could study how organizations balance economic productivity and social harmony goals to maintain perception of organizational justice (He et al, 2004; Unal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given these ethical goals are not inherently contradictory, future research may explore boundary conditions under which ethical dilemmas could be creatively resolved in a win-win fashion. For example, research could study how organizations balance economic productivity and social harmony goals to maintain perception of organizational justice (He et al, 2004; Unal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For the metro policy, the Natural Science Foundation of China called for research facilitating the establishment of harmony and innovative organizational climate. Indeed, group harmony plays the central role in enhancing team cohesion and effectiveness [49,50]. Further, Larson et al addressed that organizational climate can be shaped through intervention [51].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pecino et al (2018) found that interactional justice climate predicts work–family balance and extrarole behaviors via burnout and engagement. Ünal et al (2017) showed that interactional justice climate has a direct effect on group harmony, which in turn relates to team task and helping behaviors. Seo and Lee (2017) revealed that justice climate can act as a mechanism by which social exchange processes influence group affective tone, a concept that speaks to the dynamics and functionality of groups.…”
Section: Toxic Work Climates: a Review Of Underlying Facet-specific C...mentioning
confidence: 99%